2014
DOI: 10.1111/1756-185x.12413
|View full text |Cite
|
Sign up to set email alerts
|

Absence of protective effect of oral contraceptive use on the development of rheumatoid arthritis: a meta‐analysis of observational studies

Abstract: OC use has no protective effect on RA onset, but appears to prevent progression to severe RA. In addition, OC use has a lower protective effect on the risk of RA with change in OC composition. Finally, no cumulative effect was found between OC use and risk of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Earlier studies have demonstrated that women who have taken OCs show a modest to moderate decrease in the risk of RA, although most recent studies have not found a decreased risk, which may be attributed to the lower amount of hormones in contemporary OCs compared with the first OCs introduced in the 1960s . Nonetheless, the use of OCs was found to decrease the severity of RA in a recent meta‐analysis . Therefore, it is possible that the use of OCs influenced the disease course of RA and altered the age at RA onset.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated that women who have taken OCs show a modest to moderate decrease in the risk of RA, although most recent studies have not found a decreased risk, which may be attributed to the lower amount of hormones in contemporary OCs compared with the first OCs introduced in the 1960s . Nonetheless, the use of OCs was found to decrease the severity of RA in a recent meta‐analysis . Therefore, it is possible that the use of OCs influenced the disease course of RA and altered the age at RA onset.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding has been dose dependently associated with a decreased risk of RA in many [99][100][101][102][103][104], but not all [105] studies, whereas most investigations have reported no association between the use of oral contraceptives (OC) and RA risk [106,107]. The field is still open, however as a recent large population-based case-control study observed that ever and past use of OC were significantly associated with a decreased risk of developing ACPApositive RA and that this association was stronger for a longer duration of use [100].…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…A recent meta-analysis of five studies (two cross-sectional, one case-control, and two cohort studies) did not demonstrate any association between endometriosis and RA [ 97 ]. The pooled relative risk of the two prospective cohort studies was not statistically significant (RR = 1.46, 95% CI 0.70–3.03) [ 78 , 97 , 98 ]. Nevertheless, Harris et al found a significant association between surgically confirmed endometriosis and RA ( Table 2 ) [ 88 ].…”
Section: Reproductive Factors In Womenmentioning
confidence: 99%
“…A meta-analysis of 28 observational studies suggested a protective effect of oral contraception (OC) (ever versus never) in pooled case control studies (OR = 0.70, 95% CI 0.5–0.9) but not in pooled cohort studies (OR = 1.0, 95% CI 0.9–1.1). Current and past uses of OC were not associated with RA in pooled cohorts but there was a borderline inverse association in pooled case-control studies (past versus never OR = 0.70 and 95% CI 0.4–1.0, current versus never OR = 0.71 and 95% CI 0.5–1.0) [ 98 ]. Moreover, no dose-response association was found between OC use and risk of RA in this meta-analysis.…”
Section: Reproductive Factors In Womenmentioning
confidence: 99%